2018
DOI: 10.1177/1358863x18765667
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral artery disease, calf skeletal muscle mitochondrial DNA copy number, and functional performance

Abstract: In people without lower extremity peripheral artery disease (PAD), mitochondrial DNA copy number declines with aging, and this decline is associated with declines in mitochondrial activity and functional performance. However, whether lower extremity ischemia is associated with lower mitochondrial DNA copy number and whether mitochondrial DNA copy number is associated with the degree of functional impairment in people with PAD is unknown. In people with and without PAD, age 65 years and older, we studied associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…These results are contrasting at first glance but might be explained by the site of mtDNA‐CN measurement. McDermott et al studied local effects directly in the muscles and not systemic effects in the peripheral blood stream as we did. It is conceivable that a higher number of mitochondria might have been produced locally in the calf muscle to ensure the energy supply necessary in the weakened muscles resulting in a site‐specific increase in mtDNA‐CN .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…These results are contrasting at first glance but might be explained by the site of mtDNA‐CN measurement. McDermott et al studied local effects directly in the muscles and not systemic effects in the peripheral blood stream as we did. It is conceivable that a higher number of mitochondria might have been produced locally in the calf muscle to ensure the energy supply necessary in the weakened muscles resulting in a site‐specific increase in mtDNA‐CN .…”
Section: Discussionmentioning
confidence: 85%
“…The only other available study evaluating the role of mtDNA in PAD patients performed mtDNA‐CN measurements not in peripheral blood but in calf muscle biopsy material of 34 PAD patients and 10 controls. They found a higher mtDNA‐CN to be associated with a lower ankle‐brachial index . These results are contrasting at first glance but might be explained by the site of mtDNA‐CN measurement.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Studies that use multiple mitochondrial biomarkers have revealed only a slight intercorrelation between the markers and aging, suggesting that they tap into different biological dimensions (Lara et al, 2015;Larsen et al, 2012;Marrocco, Altieri, & Peluso, 2017;Xia, Chen, McDermott, & Han, 2017). Recent data support the hypothesis that mtDNA copy number and degree of heteroplasmy-assessed in human blood cells and in tissue biopsies-provide information on mitochondrial physiology that is relevant for aging and age-related diseases (McDermott et al, 2018;Moore et al, 2017;Zhang, Wang, Ye, Picard, & Gu, 2017). Both measurements can be utilized via PCR methods or, more recently, by derivation from genome sequencing data (Ding et al, 2015).…”
Section: Mitochondrial Functionmentioning
confidence: 83%